1993
DOI: 10.1111/j.1432-1033.1993.tb18382.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of thymosin β4 in water determined by NMR spectroscopy

Abstract: The conformational preferences of a 43-amino-acid G-actin-binding peptide, thymosin P4, in water at 1, 4 and 14°C and at pH 3.0 and 6.5 were studied by NMR. NMR showed that thymosin p4 lacks a uniquely folded conformation in water. However, some preferential a-helical conformations of thymosin /I4 can be observed in aqueous solutions. The segment at residues 5-16 showed characteristic interactions for conformations in both the P-strand and a-helical regions of the 4-y space, based on strong CH(i)-NH(i+ 1) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 34 publications
(26 reference statements)
4
60
0
Order By: Relevance
“…These proteins can either sequester monomeric actin or inhibit actin polymerization like thymosin or nucleate actin assembly like Spire, Cordon-bleu, and JMY [10]. WH2 motifs are intrinsically disordered, adopting an a-helical structure only upon binding to actin [11]. CAP in lower eukaryotes as well as mouse CAP1 are involved in cell polarity, motility, and receptor-mediated endocytosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These proteins can either sequester monomeric actin or inhibit actin polymerization like thymosin or nucleate actin assembly like Spire, Cordon-bleu, and JMY [10]. WH2 motifs are intrinsically disordered, adopting an a-helical structure only upon binding to actin [11]. CAP in lower eukaryotes as well as mouse CAP1 are involved in cell polarity, motility, and receptor-mediated endocytosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…WT, WT-like activity (ϩ), mutants that are not displayed (ND), and displayed mutants with no observed binding (Ϫ) are indicated. Second, NMR experiments showed that the motif in noncomplexed thymosin ␤4 is structurally poorly defined (17,18), whereas algorithms predict a ␣-helical conformation We show that at certain positions in the motif, some substitutions yield better or wild type binders. If we correlate this with the secondary structure propensities of these mutant amino acids (43), we can speculate on the local conformation of the hexapeptide motif in the actin bound configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Thymosin ␤4 interacts with actin via residues in an ␣-helix and a conserved hexapeptide motif (LKKTET) (14 -16). NMR studies of thymosin ␤4 reveal no unique structure for this motif; however, it is evident that the motif must become structured upon binding actin (17)(18)(19). A seemingly related sequence (LKKEKG) is present in a set of C-terminal headpiece domains (15,16) implicated in F-actin binding (20).…”
mentioning
confidence: 99%
“…In a detailed study, Vancompernolle et al (9) have shown that binding of T␤4 to actin is mainly mediated by the hexamotif LKKTET (17)(18)(19)(20)(21)(22), since loss of this sequence is paralleled by an almost complete loss of inhibitory activity. Alterations in the N-terminal part (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) of the peptide strongly influence the inhibitory activity of T␤4, whereas alterations in the C-terminal part (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) seem to be of minor importance (9). As shown by 1 H NMR spectroscopy (10, 11) T␤4 does not contain an ordered conformation in aqueous solution but tends to form an ␣-helical conformation between residues 5 and 16 (11).…”
mentioning
confidence: 99%